2021
DOI: 10.3389/fphys.2020.598628
|View full text |Cite
|
Sign up to set email alerts
|

Post-activation Performance Enhancement in the Bench Press Throw: A Systematic Review and Meta-Analysis

Abstract: Background: Mechanical power output is recognized as a critical characteristic of an athlete with regard to superior performance during a competition. It seems fully justified that ballistic exercises, in which the external load is projected into a flight phase, as in the bench press throw (BPT), are the most commonly prescribed exercises for the development of power output. In addition, the muscular phenomenon known as post-activation performance enhancement (PAPE), which is an acute improvement in strength a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 62 publications
(24 reference statements)
2
31
0
Order By: Relevance
“…Since a slight augment of performance may be the worthwhile difference between winning and losing in sport, the pre-conditioning strategies for acute athletic performance enhancement are recently of great interest for coaches and sports scientists [1][2][3][4][5][6]. In addition to the ischemic preconditioning, acute caffeine ingestion, a post-activation performance enhancement (PAPE) is well-documented as an effective method of improving voluntary dynamic activities such as throwing, running or jumping in various athletes' populations, i.e., track and field and team sports [7][8][9][10][11][12]. In practical terms, this method involves the complex execution of two similar exercises, with the first one being a high-intensity conditioning activity (CA), inducing PAPE, followed by an explosive movement.…”
Section: Introductionmentioning
confidence: 99%
“…Since a slight augment of performance may be the worthwhile difference between winning and losing in sport, the pre-conditioning strategies for acute athletic performance enhancement are recently of great interest for coaches and sports scientists [1][2][3][4][5][6]. In addition to the ischemic preconditioning, acute caffeine ingestion, a post-activation performance enhancement (PAPE) is well-documented as an effective method of improving voluntary dynamic activities such as throwing, running or jumping in various athletes' populations, i.e., track and field and team sports [7][8][9][10][11][12]. In practical terms, this method involves the complex execution of two similar exercises, with the first one being a high-intensity conditioning activity (CA), inducing PAPE, followed by an explosive movement.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, complex training is considered an effective method of integrating the development of muscle strength and power [ 16 ]. The adaptive processes following this method of training have been attributed to the long-term translation of acute enhancement in muscle contractility properties induced by CA.…”
Section: Post-activation Performance Enhancement and Complex Trainingmentioning
confidence: 99%
“…The effects of complex training have been supported by extensive research assessing its acute and chronic impact on maximum strength, muscle power, sprint, and sports performance adaptations, also in comparison with other training methods [ 16 , 17 , 18 , 19 , 20 ]. Nevertheless, some studies did not show superior effects of that method to plyometric or traditional resistance training [ 20 , 21 ].…”
Section: Post-activation Performance Enhancement and Complex Trainingmentioning
confidence: 99%
See 1 more Smart Citation
“…However, several studies verified that including a general component followed by a specific warm-up brings no extra benefits on maximal load, the number of repetitions, and fatigue index [11][12][13]. Furthermore, recent research found acute short-term performance enhancements (e.g., movement velocity in bench press throw, time under tension in the bench press) after a brief high intensity/loading conditioning exercise [14,15]. This is usually known as post-activation performance enhancement (PAPE) and it emphasizes the importance of specific warmup [16].…”
Section: Introductionmentioning
confidence: 99%